2021
DOI: 10.1007/s00429-021-02419-0
|View full text |Cite
|
Sign up to set email alerts
|

Rnd3 is necessary for the correct oligodendrocyte differentiation and myelination in the central nervous system

Abstract: Rho small GTPases are proteins with key roles in the development of the central nervous system. Rnd proteins are a subfamily of Rho GTPases characterized by their constitutive activity. Rnd3/RhoE is a member of this subfamily ubiquitously expressed in the CNS, whose specific functions during brain development are still not well defined. Since other Rho proteins have been linked to the myelination process, we study here the expression and function of Rnd3 in oligodendrocyte development. We have found that Rnd3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Our previous results demonstrated that Rnd3 deficient mice show alterations both in the structure and the function of the CNS (Mocholi et al, 2011;Ballester-Lurbe et al, 2015;Kaur et al, 2020;Madrigal et al, 2021;Marfull-Oromi et al, 2021). To determine if there were defects also at the subcellular level, we analyzed brain sections at the subventricular zone (SVZ) by electron microscopy (Figure 1A), where we had previously described several alterations (Ballester-Lurbe et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous results demonstrated that Rnd3 deficient mice show alterations both in the structure and the function of the CNS (Mocholi et al, 2011;Ballester-Lurbe et al, 2015;Kaur et al, 2020;Madrigal et al, 2021;Marfull-Oromi et al, 2021). To determine if there were defects also at the subcellular level, we analyzed brain sections at the subventricular zone (SVZ) by electron microscopy (Figure 1A), where we had previously described several alterations (Ballester-Lurbe et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously described that mice lacking Rnd3 expression show defects in the development of the CNS ( Mocholi et al, 2011 ; Ballester-Lurbe et al, 2015 ; Kaur et al, 2020 ; Madrigal et al, 2021 ). We now describe some subcellular phenotypes, such as increased content of lipid droplets and accumulation of mitochondria with irregular morphology, that might be compatible with defects in autophagy or mitophagy, as those described in neurodegenerative diseases like Alzheimer’s, Parkinson’s, Huntington’s diseases and amyotrophic lateral sclerosis ( Xu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore presumed that Rnd proteins promote myelination. Research groups, including our own, report that Rnd2 and Rnd3 are involved in the regulation of myelination, at least in part [ 25 , 50 ]. Despite the increased expression of Rnd2 protein [ 25 ], it is unclear whether Rnd3 and Rnd1 are upregulated as brain development proceeds [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research groups, including our own, report that Rnd2 and Rnd3 are involved in the regulation of myelination, at least in part [ 25 , 50 ]. Despite the increased expression of Rnd2 protein [ 25 ], it is unclear whether Rnd3 and Rnd1 are upregulated as brain development proceeds [ 50 ]. It is thought that the activities of Rnd3 and probably Rnd1, acting cooperatively with those of Rnd2, are needed to trigger myelination.…”
Section: Discussionmentioning
confidence: 99%